Untersuchung des Lösungsmitellseinflusses auf die Synthese von Manganoxid-Nanopartikeln in der Flammenspraypyrolyse - Zink, Timm Florian

Construction of A-stable explicit last-stage diagonal implicit Runge–Kutta (ELDIRK) methods - Mahnken, Rolf; Westermann, Hendrik (Computational Mechanics)
ELDIRK methods are defined to have an Explicit Last stage in the general Butcher array of Diagonal Implicit Runge-Kutta methods, with the consequence, that no additional system of equations must be solved, compared to the embedded RK method. Two general formulations for second- and third-order ELDIRK methods have been obtained recently in Mahnken [21] with specific schemes, e.g. for the embedded implicit Euler method, the embedded trapezoidal-rule and the embedded Ellsiepen method. In the first part of this paper, we investigate some general stability characteristics of ELDIRK methods, and it will be shown that the above specific RK schemes are not A-stable. Therefore, in the second part, the above-mentioned general formulations are used for further stability investigations, with the aim to construct new second- and third-order ELDIRK methods which simultaneously are A-stable. Two numerical examples are concerned with the curing for a thermosetting material and phase-field RVE modeling for crystallinity and orientation. The numerical results confirm the theoretical results on convergence order and stability.
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Digitalisierungsbezogene Lehrkräftebildung als Gegenstand internationaler Schulleistungsstudien - Domke, Marius; Fröhlich, Nadine; Eickelmann, Birgit; Pink, Sara (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Das Potenzial von Ideologiekritik im Religionsunterricht - Herdramm, Henrike (BloKK. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften)
Keywords: Ideologiekritik; Tiertheologie; Tierethik

Supporting Error Chains in Static Analysis for Precise Evaluation Results and Enhanced Usability - Wickert, Anna-Katharina; Schlichtig, Michael; Vogel, Marvin; Winter, Lukas; Mezini, Mira; Bodden, Eric
Context Static analyses are well-established to aid in understanding bugs or vulnerabilities during the development process or in large-scale studies. A low false-positive rate is essential for the adaption in practice and for precise results of empirical studies. Unfortunately, static analyses tend to report where a vulnerability manifests rather than the fix location. This can cause presumed false positives or imprecise results. Method To address this problem, we designed an adaption of an existing static analysis algorithm that can distinguish between a manifestation and fix location, and reports error chains. An error chain represents at least two interconnected errors that occur successively, thus building the connection between the fix and manifestation location. We used our tool CogniCryptSUBS for a case study on 471 GitHub repositories, a performance benchmark to compare different analysis configurations, and conducted an expert interview. Result We found that 50 % of the projects with a report had at least one error chain. Our runtime benchmark demonstrated that our improvement caused only a minimal runtime overhead of less than 4 %. The results of our expert interview indicate that with our adapted version participants require fewer executions of the analysis. Conclusion Our results indicate that error chains occur frequently in real-world projects, and ignoring them can lead to imprecise evaluation results. The runtime benchmark indicates that our tool is a feasible and efficient solution for detecting error chains in real-world projects. Further, our results gave a hint that the usability of static analyses may benefit from supporting error chains.
Keywords: Static analysis; error chains; false positive re- duction; empirical studies

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Videoanalysen zu unterrichtlichen Lehr- und Lernprozessen unter den Bedingungen der Digitalität an organisational resilienten Schulen in Deutschland - Drossel, Kerstin; Oldak, Anna; Bette, Ricarda; Eickelmann, Birgit; Schreyer, P. (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Feynman-Kac formulas for semigroups generated by multi-polaron Hamiltonians in magnetic fields and on general domains - Hinrichs, Benjamin; Matte, Oliver (arXiv:2403.12147)
We prove Feynman-Kac formulas for the semigroups generated by selfadjoint operators in a class containing Fr\"ohlich Hamiltonians known from solid state physics. The latter model multi-polarons, i.e., a fixed number of quantum mechanical electrons moving in a polarizable crystal and interacting with the quantized phonon field generated by the crystal's vibrational modes. Both the electrons and phonons can be confined to suitable open subsets of Euclidean space. We also include possibly very singular magnetic vector potentials and electrostatic potentials. Our Feynman-Kac formulas comprise Fock space operator-valued multiplicative functionals and can be applied to every vector in the underlying Hilbert space. In comparison to the renormalized Nelson model, for which analogous Feynman-Kac formulas are known, the analysis of the creation and annihilation terms in the multiplicative functionals requires novel ideas to overcome difficulties caused by the phonon dispersion relation being constant. Getting these terms under control and generalizing other construction steps so as to cover confined systems are the main achievements of this article.

Post-configuration Activation of Hardware Trojans in FPGAs - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Journal of Hardware and Systems Security)
Keywords: General Engineering; Energy Engineering and Power Technology

Walking with Images: Mimetic-Automatic Production in Hasan Elahi’s Tracking Transcience - Althoff, Sebastian (Walking with the Enemy: Reclaiming the Language of Power and Manipulation in the Post-Truth Era)